(untitled) (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
The purpose of this study was to learn about the types of code mixing, the dominant type of code mixing, and teacher’s reasons used code mixing in classroom interaction at SMP N 1 Karangawen. The authors utilized a descriptive qualitative method to analyze code mixing in this study. The eighth grade English teachers at SMP N 1 Karangawen was the subject of this investigation. The data for this study was gathered through interviews and observation. The findings revealed that English teachers employed three types of code mixing in classroom interactions: intra sentential code mixing, intra lexical code mixing, and invoving change of pronunciation. The dominant type of code mixing utilized by teachers in classroom interaction was intra sentential code mixing, there were 138 expressions that included intra sentential code mixing (83.6%), 23 expressions that involved intra lexical (14%) and 4 expressions that involved change of pronunciation (2.4%). While teachers employed code mixing in classroom interaction for talking about a particular topic, interjection, and repetition were used for clarification.